الأمن الصحي كمكوّن من مكوّنات الأمن المجتمعي - زان مريم (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تتناول هذه الورقة البحثية موضوع الأمن الصحي باعتباره من المكونات الأساسية للأمن المجتمعي، فقد أصبح الأمن الصحي من أهم المواضيع المطروحة على الأجندة السياسية الدولية، نظرا لأهمية الصحة ودورها في منظومة الأمن الانساني وفي توليفة التنمية المجتمعية الشاملة، ولقد توصلنا الى أنّ دول العالم أصبحت تعمل بشكل متزايد على تحقيق الأمن الصحي الذي يواجه تحديات وتهديدات عدة يمكن أن تحدث حالة من اللاأمن الصحي والذي يؤثر سلبا على الأمن المجتمعي من خلال تداعياته السياسية والاقتصادية والاجتماعية. Abstract: The Copenhagen School for Peace and Security Research contributed to expanding the concept of security to include societal security, which Barry Buzan described as one of the most complex of security, In contrast to the emergence of new sources of security threats of an asymmetric nature and unequal power, such as organized crime, whose impact has gone beyond the which is the subject of this research paper, which is addressed by asking the following problem: What are the repercussions of organized crime in its various forms on societal security in Algeria?. Keywords: community security; Organized crime; Asymmetric threats